The effect of nutrients in anodic chamber to the performance of microbial fuel cell (MFC) - Nashley Ursula Mundi Ujai; Siti Kudnie Sahari; Marini Sawawi; Kuryati Kipli; Asmahani Awang; Mohamad Rusop Mahmood; Lilik Hasanah; Abdul Rahman Kram; Zainab Ngaini (Universiti Putra Malaysia, 2024)
This paper describes a device known as a Single-chamber Microbial Fuel Cell (SMFC) that was used to generate bioelectricity from plant waste containing lignocellulosic components, such as bamboo leaves, rice husk and coconut waste, with various anodic chamber substrate compositions. The maximum power density among all assembled SMFCs was determined to be 231.18 µW/m2 , generated by coconut waste. This model’s bioelectricity production was enhanced by adding organic compost to the anodic chamber, which acts as a catalyst in the system. The maximum power density of 788.58 µW/m2 was attained using a high proportion of coconut waste (CW) and organic compost. These results show that the higher percentage of lignin in CW improved the bioelectricity of SMFC.